Kualitas Dan Daya Simpan Ikan Nila Dan Ikan Kakap Merah Dengan Menggunakan Daun Sirih Hijau Sebagai pengawet Alami - Pertiwi, Rusmawati Dewi; , Dra.Titik Suryani, M.Sc (2016)
Tilapia and red snapper is a food that contains fairly high nutritional and beneficial for health, but the fish began to decline after two hours of quality physical death caused by microorganisms .Green betel leaf contains flavonoids , phenols , thiamine , and tannins that can inhibit microbial activity .The purpose of this study on the abundance of bacteria , moisture content , pH , organoleptic test, quality, and storability on tilapia and red snapper with green betel leaf extract concentration different. This research method using a completely randomized design (CRD) with two factors, first the type of fish (J1= tilapia, J2 = red snapper) and factor 2 is the concentration of betel leaf extract of green (K1 = 40 %, K2 = 50 %, K3= 60 % ) with 6 treatments .The results showed that the quality of the best fish preservation is in treatment J2K3 (120 g red snapper and green betel leaf extract 60 % ) , with a population of bacteria 43 x 105 cfu / g , the water content of 42.34 % and a pH of 6.6, with clear and bright appearance, aroma of fresh betel leaf green, dense and supple texture, color brownish red gills, eyes bulging and storability 18 hours and still be consumed